Vitamin D in Autoimmunity: Molecular Mechanisms and Therapeutic Potential - Dankers, Wendy; Colin, Edgar M.; van Hamburg, Jan Piet; Lubberts, Erik (Frontiers in Immunology, 2017)
Over the last three decades it has become clear that the role of vitamin D goes beyond the regulation of calcium homeostasis and bone health. An important extra-skeletal effect of vitamin D is the modulation of the immune system. In the context of autoimmune diseases, this is illustrated by correlations of vitamin D status and genetic polymorphisms in the vitamin D receptor with the incidence and severity of the disease. These correlations warrant investigation into the potential use of vitamin D in the treatment of patients with autoimmune diseases. In recent years several clinical trials have been performed to investigate the therapeutic value of vitamin D in multiple sclerosis, rheumatoid arthritis, Crohn’s disease, type I diabetes and systemic lupus erythematosus. Additionally, a second angle of investigation has focused on unraveling the molecular pathways used by vitamin D in order to find new potential therapeutic targets. This review will not only provide an overview of the clinical trials that have been performed, but also discuss the current knowledge about the molecular mechanisms underlying the immunomodulatory effects of vitamin D and how these advances can be used in the treatment of autoimmune diseases.